1964
DOI: 10.1126/science.145.3627.63
|View full text |Cite
|
Sign up to set email alerts
|

5-Methoxytryptophol: Effect on Estrus and Ovarian Weight

Abstract: Daily injection of 5-methoxytryptophol in microgram quantities in rats decreased the incidence of estrus and reduced ovarian weight in maturing animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1970
1970
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…This compound is formed in the pineal gland from 5-hydroxytryptophol and reduces ovarian weight as well as decreasing estrus in maturing rats (47). Delvigs et al (46) suggest it is rapidly metabolized (as indicated by radioactivity in the urine), and additionally showed high levels in thyroid, adrenals, ovaries, and uterus.…”
Section: Methodsmentioning
confidence: 99%
“…This compound is formed in the pineal gland from 5-hydroxytryptophol and reduces ovarian weight as well as decreasing estrus in maturing rats (47). Delvigs et al (46) suggest it is rapidly metabolized (as indicated by radioactivity in the urine), and additionally showed high levels in thyroid, adrenals, ovaries, and uterus.…”
Section: Methodsmentioning
confidence: 99%
“…5-Methoxytryptophol inhibits a wide range of test models used to evaluate reproductive competency in female mammals (Vaughan, 1981), Injections of ML can decrease ovarian weight and the frequency of estrus in rats (McIsaac et al, 1964), delay the onset of puberty in rats (Fraschini et al, 1975), inhibit compensatory ovarian hypertrophy in mice (Vaughan et aL, 1972), inhibit HCG-induced hypertrophy of the gonads and uterine weight in mice (Hipkin, 1970;Vaughan et aL, 1976) and modestly inhibit coitus-induced ovulation in rabbits (Farrell et aL, 1968). In the present study, female hamsters treated with ML for 7 weeks had decreased pituitary and increased plasma concentrations of prolactin.…”
Section: Discussionmentioning
confidence: 99%
“…The responses of the reproductive system and plasma levels of thyroid hormones to afternoon injections ofaML and ML have been tested in the male hamster but never in the female Vaughan et al, 1983). Earlier reports, however, suggest that aML and ML may have important inhibitory effects on the estrous cycle of rats (McIsaac et al, 1964;Taborsky and Delvigs, 1966). Thus, we decided to examine the role of aML and ML on the endocrine system of the female Syrian hamster and to compare the effects obtained with those previously described for melatonin Trakulrungsi et al, 1979).…”
Section: Introductionmentioning
confidence: 97%
“…Melatonin and 5-methoxytryptophol are both involved in the regulation of reproduction, and both have been observed to show stimulatory (Thi~blot et al, 1966;Balemans, 1973) as well as inhibitory (Wurtman et al, 1963;Mclsaac et al, 1964;Balemans et al, 1977 a, b) effects. Therefore it seemed of interest to perform experiments in which the influence of white, red and green light in a light/dark rhythm on the circadian rhythmicity of N-and O-acetyltransferase activity would be studied.…”
Section: Introductionmentioning
confidence: 95%